Cross-sectional analysis of shooting distance of futsal players in Indonesian futsal league matches - Elumalai, Gunathevan (Tanjung Malim, 2023)
Cross-sectional analysis of shooting distance of futsal players in Indonesian futsal league matches by Elumalai, Gunathevan